Geography and math teachers in distance learning education amid COVID-19 pandemic in Albania - Dhimitri, Jostina (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2021)
The Coronavirus 2019 pandemic (COVID-19) brought a rapid change in the professional routine of in-service teachers worldwide. The study presents an assessment of challenges of online distance learning where a sample group of 155 geography and mathematics teachers, in pre-university system in Albania were involved during the first periods of the COVID-19 pandemic. The research found that lack of prior preparation has significantly affected the selection and usage of platforms, suitable for distance learning. Teachers face more difficulties in cartographic, graphic and symbolic semantic and less in verbal one. At the beginning of the pandemic, teaching was done mostly through WhatsApp and further on with the RTSH TV channels, followed by Google Classroom and Zoom. Teachers have fulfilled the needs for technological training through cooperation with colleagues and self-training and through various tutorials. The study emphasizes that teachers need professional development especially in soft ware systems and online teaching methodologies.
Keywords: Albania; Albanija; COVID-19; distance teaching; geography of education; izobraževanje na daljavo; pandemic; pandemije; šolska geografija